Studies on adhesion of polyamide 6 to microwave-plasma-modified polypropylene - Gancarz, I.; Pigłowski, J. (Polimery, 2022)
Isotactic PP plates were treated with microwave plasma generated from nonpolymerizing gases, viz., nitrogen, air, ammonia, argon, and carbon dioxide. The surface tension of PP was examined in relation to plasma treatment time and distance of the plate from the plasma front. In the PP plate, surface tension was found to rise from 28 to 40-45 mN/m. The effect of plasma treatment, viz., hydrophilization of the PP surface, was attained within a short time (0.5 min); protraction of the treatment did not result in an essential increase in surface tension (Fig. 2). The treatment was most effective when the source of plasma was placed close to the surface of the plate (Fig. 5). The strength of modified PP-PA 6 joints was found to be directly related to the surface tension of modified PP (Fig. 7). The work of adhesion evaluated from thermodynamic data was similar to that estimated from adhesive bond strength measurements (Table 1). The space to accomodate the fluctuations resulting in the destruction of the adhesive joint, estimated from strength measurements to be 61 nm3 was quite close to the 53 nm3 evaluated from lifetime measurements.